Computational fluid dynamics and experimental study of hydrodynamics in an internal airlift reactor - Liew, Shi Yan (2019)
Gas-liquid airlift reactors have recently garnered interest from renewable energy and wastewater treatment industries, prompting the adoption of flexible computational method to elevate existing conventional scale-up constraints. Most gas-liquid simulation studies employed the two-fluid model owing to its computational affordability. However, the model’s predictive capability depends on a proper choice of closure model to account the momentum exchange forces between the gas-liquid interphase lost during the trade-off. Hence, the main aim of this work is to develop a computational fluid dynamics (CFD) modelling approach in the gas-liquid internal airlift reactor via two-fluid model by elucidating the closure model. This study was divided into two main parts. Firstly, an assessment of the closure model on mean flow quantities was carried out in an internal airlift reactor with gas partially disengaged in the downcomer. The simulation employs the dispersed standard k-ε turbulence model through the Eulerian-Eulerian multiphase model to resolve the 3D transient flow field. The closure model elucidated in this work comprised of drag, lift, turbulent dispersion and bubble-induced turbulence forces. Results show that the hydrodynamics was accurately predicted when bubble distortion and bubble swarm were considered in the drag coefficient through the Rayleigh-Taylor model. Mean flow quantities predicted by the closure model were validated against literature data on surface-averaged gas holdup, radial gas holdup and radial liquid velocity of the flow field obtaining mean errors of 19.4%, 6.8% and 13.5%, respectively. Second part of this study extends the assessment of the closure model to an internal airlift reactor with total gas disengagement in the downcomer. The modelling approach employs the Eulerian-Eulerian two-fluid model with the same turbulence model. Comparison studies on different drag, the effect of lift and turbulent dispersion model were carried out to examine the mean axial liquid velocity in the riser and downcomer. Predicted results were validated against laser Doppler anemometry (LDA) measurements obtained from a fabricated experimental rig. It was found that the axial liquid velocity in the riser was severely under-predicted by the spherical drag model. In this study, the simulation results showed a margin error 52.7% when the Rayleigh-Taylor, lift and turbulent dispersion model was employed. Overall, the simulation results obtained reasonable agreement with experimental data with error less than 20% on local gas distribution results through the Rayleigh-Taylor drag model, lift model as a function of Reynolds and Eӧtvӧs number and drift velocity turbulent dispersion model. However, the modelling approach in this study is limited to bubbly homogeneous flow due to the absence of mathematical models to account the bubble dynamics in heterogeneous flow. In addition, the effects of sparger location on the flow field was also being evaluated using LDA measurement technique. It was found that the sparger with position XA = 0.125 m is more energy efficient than sparger with position XB = 0.075 m as the latter which is located slightly nearer to the baffle wall was producing recirculation flows within the downcomer and lower magnitudes of liquid velocity in the downcomer was observed.